The Influence of Emerging Technologies on Human Conduct - Choudhary, Krishna Chandra; Rawat, Narinder Singh (JOURNAL OF INDIAN EDUCATION, 2023)
Not just in India but globally, technology has become the pillar of society. Almost everyone in today’s culture spends between three and four hours a day online, whether they are students or full-time employees. Individuals and vocations vary greatly in their dependence on technology. Numerous experts hypothesised that students would be more impacted by the negative impacts of modern technologies on human behaviour than the working population as a whole. According to a recent study, adolescents (those between the ages of 10 to 19) overuse the internet. Adolescents use their phones to play games and play with friends. Mental health practitioners have taken serious note of the disturbing behaviours, psychological disorders, and mental health challenges of the younger generation. Due to their addiction to technology, young people nowadays abuse and overuse online apps built for mobile devices. Numerous studies have shown that internet addiction poses the greatest threat to human life. People from many areas of life may be badly affected by excessive internet use, regardless of age. It muddles the objectives of the next generation. Internet addiction may inhibit personal growth and have detrimental impacts on health and relationships. A person’s health and relationships may deteriorate if they spend too much time online.